Type H vessels: functions in bone development and diseases - Liu, Xiaonan; Zhang, Peilin; Gu, Yuan; Guo, Qiaoyue; Liu, Yonggan (Frontiers in Cell and Developmental Biology, 2023)
Type H vessels are specialized blood vessels found in the bone marrow that are closely associated with osteogenic activity. They are characterized by high expression of Endomucin and CD31.Type H vessels form in the cancellous bone area during long bone development to provide adequate nutritional support for cells near the growth plate. They also influence the proliferation and differentiation of osteoprogenitors and osteoclasts in a paracrine manner, thereby creating a suitable microenvironment to facilitate new bone formation. Because of the close relationship between type H vessels and osteogenic activity, it has been found that type H vessels play a role in the physiological and pathological processes of bone diseases such as fracture healing, osteoporosis, osteoarthritis, osteonecrosis, and tumor bone metastasis. Moreover, experimental treatments targeting type H vessels can improve the outcomes of these diseases. Here, we reviewed the molecular mechanisms related to type H vessels and their associated osteogenic activities, which are helpful in further understanding the role of type H vessels in bone metabolism and will provide a theoretical basis and ideas for comprehending bone diseases from the vascular perspective.